Strategi Implementasi Kurikulum Merdeka Pada Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Dalam Menghadapi Tantangan Pendidikan Kontemporer - Imran; Tohet, Moch.; Mahbubi, M (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to describe the implementation of the Independent Curriculum in Islamic Religious Education (PAIBP) learning at SMP Negeri 2 Pakuniran, and to identify the challenges and strategies implemented to address the dynamics of education in the era of globalization. Using a qualitative approach with a case study method, data were collected through in-depth interviews with the principal, Islamic Religious Education (PAIBP) teachers, and students, accompanied by direct observation and supporting documentation. The results show that the Independent Curriculum has been implemented through a student-centered, project-based, reflective, and contextual learning approach. Students are encouraged to increase their independence through Islamic activity journals, thematic discussions, and involvement in social projects. The use of learning technologies, such as e-learning platforms and online quiz applications, is an important strategy in increasing learning motivation and digital literacy. Furthermore, spiritual and social values, as well as the integration of science and religion, are also emphasized in the learning process. However, several obstacles remain, such as teachers' limited understanding of differentiated learning planning, unequal digital literacy, and limited facilities and infrastructure. This study highlights the gap between the ideals of the Independent Curriculum and the real conditions in schools in rural areas. However, the implementation of this curriculum still has a positive impact on character formation, strengthening Islamic values, and preparing students to face the challenges of the times. These findings provide theoretical and practical contributions to strengthening the implementation of the Independent Curriculum in non-urban areas